EFEKTIVITAS PENGGUNAAN STRATEGI TUTOR SEBAYA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS X DI MADRASAH ALIYAH SUMBER BUNGUR PAKONG PAMEKASAN - Hadinata, Sofyan; Munib, Abdul; Haris, Abd; Atnawi, Atnawi (Journal of Education Partner, 2024)
Madrasah Aliyah Sumber Bungur Pakong Pamekasan has implemented a peer tutoring strategy in the class X Aqidah Morals subject which has an impact on student learning achievement. There are two main problems in this research. First, the effectiveness of using peer tutoring strategies can increase student achievement in the class X Aqidah Morals subject. Second, supporting and inhibiting factors in the use of peer tutoring strategies in improving student learning achievement in the class X Aqidah Akhlak subject. This research uses a qualitative descriptive approach. The research results were obtained in the form of descriptive data. Meanwhile, the data sources for this research are Aqidah Akhlak subject teachers, and also class X students, both Mathematics and Natural Sciences and Social Sciences. The data analysis was carried out using a qualitative descriptive method, namely reducing, presenting, and verifying the data. The results of research conducted by researchers relate to the use of peer tutoring strategies in improving student learning achievement in the Aqidah Akhlak class X subject. The peer tutoring strategy selects superior, intelligent, and accomplished students to become tutors. Previously, the teacher explained the material first to the tutor so that it was easy to master the material grid when carrying out the tutorial. While tutoring activities are taking place, the teacher supervises and evaluates by giving independent assignments. The use of peer tutoring strategies in subjects in class X turned out to be very effective in improving student learning achievement. Students are more enthusiastic about improving their learning achievements and interact more easily with tutors. Its effectiveness seems to be increasing, the average score is perfect, namely 86 or A. So, the peer tutoring strategy has an effect on learning achievement, initially the score was equivalent to the KKM (Minimum Completeness Criteria) score, namely B and only part of the students mastered the material. However, after peer tutoring, the achievement exceeded the KKM, namely A. This achievement was strengthened by the even distribution of high scores among all students from each class. The supporting factors are that students are more enthusiastic about learning and have easier interactions. Meanwhile, the inhibiting factor in using peer tutoring strategies is internal factors with a lack of awareness among students of the importance of the subject matter. Meanwhile, external factors include inadequate facilities and infrastructure to support the learning process.